2019
DOI: 10.1089/wound.2019.1028
|View full text |Cite
|
Sign up to set email alerts
|

Wound Closure Outcomes Suggest Clinical Equivalency Between Lyopreserved and Cryopreserved Placental Membranes Containing Viable Cells

Abstract: Objective: To evaluate the clinical outcomes of lyopreserved placental membrane containing viable cells (vLPM) in the treatment of nonhealing wounds of various etiologies, and to compare them to those previously reported for cryopreserved placental membrane containing viable cells (vCPM). Approach: Patients with nonhealing wounds who qualified to receive advanced wound therapies were consecutively enrolled and treated weekly with vLPM plus standard of care (SOC) at five centers. Data were de-identified and ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
2
14
0
3
Order By: Relevance
“…They have collagen-rich extracellular matrix proteins, providing growth factors, glycosaminoglycans, fibroblasts and epithelial cells, and important mesenchymal stem cells. In vitro placental membranes promote cellular adhesion and migration, cell differentiation, and proangiogenic anti-inflammatory activities and protect growth factor function [ 155 , 156 ]. One randomized controlled trial evaluated dehydrated human placental allograft (dehydrated human amnion chorion membrane, dHACM) in patients with VLU [ 157 ].…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…They have collagen-rich extracellular matrix proteins, providing growth factors, glycosaminoglycans, fibroblasts and epithelial cells, and important mesenchymal stem cells. In vitro placental membranes promote cellular adhesion and migration, cell differentiation, and proangiogenic anti-inflammatory activities and protect growth factor function [ 155 , 156 ]. One randomized controlled trial evaluated dehydrated human placental allograft (dehydrated human amnion chorion membrane, dHACM) in patients with VLU [ 157 ].…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…Grafix must be stored at À80°C before use and has a 3-year shelf life. 72,73 Given the cryopreservation, Grafix preserves the structural and cellular integrity of the amnion and chorion and is a true alternative to fresh placental membranes. 74 A multicenter, blinded randomized control trial found that by week 12, 62% of Grafix-treated DFU patients closed their wounds versus 21% of standard-of-care patients treated with surgical debridement and nonadherent dressings (p ¼ 0.0001).…”
Section: Cellular Skin Substitutesmentioning
confidence: 99%
“…A recent study found that patients treated with lyopreserved grafts averaged a wound closure rate of 59.2%, suggesting clinical equivalency to the cyropreserved counterpart. 73…”
Section: Cellular Skin Substitutesmentioning
confidence: 99%
“…RCTs using cryopreserved and lyopreserved AM have shown a higher proportion of closure in the treatment of DFUs and faster closure compared with standard treatments in RCTs 16 . Using the lyopreserved construct, Ananian showed wound closure rates of 65.8% in DFU that had been present for <12 months with median time to closure of 63 days 17 …”
Section: Introductionmentioning
confidence: 99%
“…16 Using the lyopreserved construct, Ananian showed wound closure rates of 65.8% in DFU that had been present for <12 months with median time to closure of 63 days. 17 In this paper, we report the results of a bench study of cellular viability of cryo-and lyopreserved amniotic tissue samples and the clinical outcomes of a 12-week cohort study. The primary outcome of the study was the proportion of ulcers that achieved closure during treatment.…”
mentioning
confidence: 99%